: Stunting Among School-Aged Children in West Bandung: Social Determinants from a Locus Area Perspective - Isti Kumalasari; Ahmad Hisbullah Amrinanto (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Stunting remains a significant chronic nutritional problem in Indonesia, particularly among children born to adolescent mothers. These young mothers often face limitations in nutritional knowledge, lower health literacy, and suboptimal reproductive preparedness, which collectively increase the risk of stunting in their children. Objective : This study aimed to conduct a review to determine the association between adolescent mothers’ nutritional knowledge and the incidence of stunting in toddlers, and to identify the contributing factors. Research Methods/ Implementation Methods : This was a systematic review conducting following the PRISMA guidelines and utilizing the Population, Concept, and Context (PCC) framework. Articles were collected through searching the Scopus, PubMed, Google Scholar, and Crossref databases for studies up to October 2025. Two reviewers independently screened and included full- text article that examined Mothers Knowledge and stunting, focusing on the concept of knowledge, adolescent mother, and stunting. Results : A review included five articles. Adolescent mothers’ knowledge had a significant association with the incidence of stunting. This association was often strengthened by confounding factors such as socio-economic status, low education levels, limited access to healthcare services, and inadequate childcare practices. Several studies found that improving maternal nutritional literacy and initiating early prenatal care can effectively reduce the risk of stunting in children. Conclusion/Lesson Learned : Low nutritional knowledge among adolescent mothers is confirmed as an important determinant of stunting in toddlers. Intervention efforts need to be focused on enhancing the education and nutritional literacy of adolescent girls through structured programs, including school-based education, adolescent mother classes in community health centers (Puskesmas), and targeted community campaigns. The integrated approach is crucial to break the intergenerational cycle of stunting and foster the development of quality human resources.